KORELASI ADVERSITY QUOTIENT DENGAN PRESTASI NILAI SKOR TOSM PADA PENGURUS OSIS SMK - Ade Machnun Saputra; Rini Sugiarti (Jurnal Psikohumanika, 2021)
This study aims to empirically test the influence of adversity quotient on the achievement of ToSM (test of second mathematics) scores on the student. The hypothesis proposed is the influence of adversity quotient on the accomplishment of ToSM scores on students. The subjects in this study amounted to 34 students from SMK Negeri 1 Dukuhturi, Tegal Regency. The sampling technique used is saturated sampling. The measuring instruments in this study were adversity quotient scales and Android app-based ToSM. The results of this study showed the significance of the correlation test was 0.671 > 0.05 and Pearson correlation = 0.075 < r table = 0.3246, while the linearity test explained the magnitude of the correlation value / R relationship of 0.75 of the output obtained a coefficient of determination (R Square) of 0.006, which contains the understanding that the influence of Adversity Qutotien variable on variable performance ToSM score value is 0.6%, the data can be interpreted that there is no correlation between the variables studied, these findings can also be interpreted that to increase KHDI is not enough just by relying on adversity intelligence alone need other efforts.